Pengaruh Penggunaan Media Kolase berbahan Alam Terhadap Perkembangan Motorik Halus Anak Usia 5-6 Tahun di PAUD Telkom Ternate - Husen, Winda Nifia; Sahidun, Nurfitri (Peneliti.net, 2024)
The aim of this research is to find out whether there is an effect of using natural collage media on children's fine motor development. The formulation of the research problem is as follows: